Zgoda na przysposobienie - Panowicz-Lipska, Janina (Wydział Prawa i Administracji UAM, 1985)
According to Family and Guardianship Code (F.G.C.), adoption is realized by means of guardianship count decision on demand of am adopter. Unless it is otherwise provided by law, consent of specified persons is indispensable for adoption i.e.: consent of an adoptee when he turned thirteen, consent of his parents, of a guardian or an adopter's spouse if both spouses are not adopting jointly. The consent of 'the said persons as an element of adoption's effectuation is characterized by the fact that it is not creating the relationship of adoption but consists one of the premises of admissibility of deciding adoption by court. There are numerous question open to discussion related to the consent to adoption as a material premise of an adoption decision. One of those of a general impact for the whole institution of consent to adoption as well as related to the consent's positioning in a construction of adoption's realization is discussed in the article. It is a question of establishing legal character of a declaration of consent to adoption. That issue has not yet been satisfactirily clarified in the doctrine and jurisdiction of the Supreme Court. Particularly, the commonly adopted treatment of the consent as a declaration of will (legal (transaction) in the understanding of Civil Code (C.C.) must raiseobjections. That view can be /traced to a psychological concept of declaration of will according to which the declaration of will means as much as manifesting an intention to cause legal consequences. The reason for doubts lies in the nature of ;legal transaction an indispensable element of which is a declaration of will; the fürst is considered to be a (particular element of civil daw system provided for the legal subjects to form independently binding legal relations. Whereas no results turning into a change of previous legal situation of -the subjects are observed with making a statement of consent to adoption. Consequently it can be advocated that the institution of legal transaction (declaration of will) is not applicable in the system of adoption instituted judicially and admitted by F.G.C, for the reason of inadequacy of its function to the statutorily set role of a declaration of consent to adoption. The appraisal of a declaration of consent in the light of the newer concept of declaration of will as a normative statement instituting an individual norm of behavior is positively speaiking against considering the consent to adoption to be a declaration of will. Referring to the theory of conventional acts, which generated the aforementioned concept, it can be maintained that a sense of declaration of consent to adoption as a conventional act of legal consequence consists entirely in creating a situation in which a formerly laid down norm becomes applicable ana duties of court in a shape of an adequate reaction to that act would actualize thenselves. The results of study of the C.C. regulation of legal transactions to solve quétions related to consent to adoption prove that it is of little avail what is ia
The consent to adoption